Estudio, análisis y propuesta de solución al congestionamiento vehicular en los jirones Salaverry, Orellana y Shapaja, comprendido entre las intersecciones de los jirones 1° de Mayo y Salaverry hasta los jirones Sahapaja y Jiménez Pimentel de la ciudad de Tarapoto, distrito de Tarapoto, provincia y región San Martín - Huamán Julca, Gean (2016)
Society seems to have become aware that, in general; transportation issues are not only manifested in more areas, they have acquired greater severity, in countries both industrialised ~ cqmo in the developing. In recent years the increase in the demand for transport and road traffic have brought such as consecuenGia, particl llarmente in lªs large giugades, increases in congestion, delays, accidents and environmental problems, quite larger than those considered acceptable by the citizens. The increase in explosive phenomena is due to the ease of growing access to automobiles, resulting from the increase in the purchasing power of the socioeconomic classes of middle income, greater access to credit, the relative reduction of prices, a higher offer for recycling of used cars, the growth of the population, the reduction in the number of people per household and the poor implementation of policies ~ ~ tn. JQturadas in the are...